Behavioral Reluctance in Adopting Open Access Publishing: Insights From a Goal-Directed Perspective - Köster, Massimo; Moors, Agnes; De Houwer, Jan; Ross-Hellauer, Tony; Van Nieuwerburgh, Inge; Verbruggen, Frederick (Frontiers in Psychology, 2021)
Despite growing awareness of the benefits of large-scale open access publishing, individual researchers seem reluctant to adopt this behavior, thereby slowing down the evolution towards a new scientific culture. We outline and apply a goal-directed framework of behavior causation to shed light on this type of behavioral reluctance and to organize and suggest possible intervention strategies. The framework explains behavior as the result of a cycle of events starting with the detection of a discrepancy between a goal and a status quo and the selection of behavior to reduce this discrepancy. We list various factors that may hinder this cycle and thus contribute to behavioral reluctance. After that, we highlight potential remedies to address each of the identified barriers. We thereby hope to point out new ways to think about behavioral reluctances in general, and in relation to open access publishing in particular.